The Valuation of Discontinued Operations and Its Effect on Classification Shifting - Kaplan, Steven E.; Kenchington, David G.; Wenzel, Brian S. (The Accounting Review, 2020)
ABSTRACT Research documents that firms shift operating expenses into income-decreasing, but not income-increasing, discontinued operations. We argue that valuation considerations explain this asymmetric result, as acquirers are likely to value the earnings of income-increasing discontinued operations more highly than the earnings of income-decreasing discontinued operations. Using a large sample of hand-collected data, we show that pre-tax earnings and operating expenses are significantly more value-relevant for income-increasing discontinued operations, supporting our economic explanation for why firms do not shift operating expenses into income-increasing discontinued operations. Additional analysis shows that in situations where managers are constrained from shifting operating expenses due to valuation concerns, they shift tax expense (an expense that is less value-relevant) from continuing operations into income-increasing discontinued operations. Overall, we conclude that valuation considerations constrain firms from shifting operating expenses into income-increasing discontinued operations, but do not constrain firms shifting tax expenses.